Inventory of dragonflies in the Curug Panjang Waterfall area, Muara Beliti District, Musi Rawas Regency - Windy Noviyana; Merti Triyanti; Mareta Widiya (Journal on Biology and Instruction, 2021)
There are many kinds of fauna in the waterfall Curug Panjang Muara Beliti, Musi Rawas Regency. One of the types of fauna found in this area is insects. Dragonflies is insects whose habitats live in water and in the air. This study aims to determine the types of dragonflies and abiotic factors carried out in the Curug Panjang waterfall area by using purposive sampling method. Data collection techniques are observation, documentation and identification. Sampling using insects net. The results of the study have been obtained by 2 sub-orders, 4 families and 12 different species namely Diplacodes trivialis, Orthetrum pruinosum, Orthetrum sabina, Orthetrum pruinosum, Crocothemis servillia, Neurothemis ramburii, Trithemis aurora, Pantala flavescens, Tholymis tillarga, Orthetrum pruinosum, Crocothemis servillia, Neurothemis ramburii, Trithemis aurora, Pantala flavescens, Tholymis tillarga, Ictinogrius, Agriocnemis pygmaea, and Copera marginipes. Abiotic factor measurement results are with an average air temperature of 27,75ËšC, 76% air humidity and 396,5 lux light intensity.